Quality of Life in Brain Cancer: Clinical Validation of the Mexican-Spanish Version of the EORTC QLQ-BN20 Questionnaire - Cacho-Díaz, Bernardo; Lorenzana-Mendoza, Nydia A.; Oñate-Ocaña, Luis F. (Frontiers in Neurology, 2019)
Background: Overall survival (OS) of patients with Brain Cancer (BC) is slowly increasing. The disease itself and its treatments deeply impact patient Health-related quality of life (HRQL). Therefore, valid and reliable instruments are needed. In this study, the Mexican-Spanish version of the psychometric and clinical validation of the QLQ-BN20 instrument is presented. Methods: Patients with brain cancer (BC) (primary or metastatic) evaluated at a tertiary cancer center, were invited to respond to the questionnaire, as well as the core-module QLQ-C30. Tests to demonstrate the instrument´s internal consistency, the association of HRQL scales with clinical variables and OS were investigated. Results: One hundred nineteen patients were included in this cohort: 77 women and 42 men (mean age, 46.2 years). Patients answered both instruments in <30 minutes. Good convergent [all correlation coefficients (CC) >0.37] and discriminant validity was observed and was associated with significant overlap (CC 0.0070.68). All four multi-item scales of QLQ-BN20 also demonstrated good reliability (Cronbach α >0.7). Several scales of the QLQ-BN20 were significantly associated with performance status and a modified Recursive Partition Analysis. Of the possible scale correlations, 40 of 161 (24.8%) scales in both instruments, were significantly (directly or inversely) correlated. Visual disorders, Motor dysfunction, Seizures and Weakness of the legs presented association with OS (p<0.05). Conclusion: The Mexican-Spanish version of the BN20 instrument is valid and reliable and can be used in clinical trials in patients with BC. Some HRQL scales were associated with OS and could therefore be incorporated in future studies of prognostic models.